Transition metal-catalysed A-ring C-H activations and C(sp2)-C(sp2) couplings in the 13α-oestrone series and in vitro evaluation of antiproliferative properties - Péter Traj; Ali Hazhmat Abdolkhaliq; Anett Németh; Sámuel Trisztán Dajcs; Ferenc Tömösi; Tea Lanisnik-Rizner; István Zupkó; Erzsébet Mernyák (Taylor & Francis Group, 2021)
Facile syntheses of 3-O-carbamoyl, -sulfamoyl, or -pivaloyl derivatives of 13α-oestrone and its 17-deoxy counterpart have been carried out. Microwave-induced, Ni-catalysed Suzuki-Miyaura couplings of the newly synthesised phenol esters with phenylboronic acid afforded 3-deoxy-3-phenyl-13α-oestrone derivatives. The carbamate and pivalate esters proved to be suitable for regioselective arylations. 2-(4-Substituted) phenyl derivatives were synthesised via Pd-catalysed, microwave-assisted C-H activation reactions. An efficient, one-pot, tandem methodology was elaborated for the introduction of the carbamoyl or pivaloyl group followed by regioselective C-2-arylation and subsequent removal of the directing group. The antiproliferative properties of the novel 13α-oestrone derivatives were evaluated in vitro on five human adherent cancer cell lines of gynaecological origin. 3-Sulfamate derivatives displayed substantial cell growth inhibitory potential against certain cell lines. The newly identified antiproliferative compounds having hormonally inactive core might be promising candidates for the design of more active anticancer agents.